2017
DOI: 10.1111/acps.12797
|View full text |Cite
|
Sign up to set email alerts
|

Increased illness burden in women with comorbid bipolar and premenstrual dysphoric disorder: data from 1 099 women from STEP‐BD study

Abstract: Objective The impact of co-morbid Premenstrual Dysphoric Disorder (PMDD) in women with bipolar disorder (BD) is largely unknown. We compared illness characteristics and female-specific mental health problems between women with BD with and without PMDD. Method 1,099 women with BD who participated in the Systematic Treatment Enhancement Program for Bipolar Disorder (STEP-BD) were studied. Psychiatric diagnoses and illness characteristics were assessed using the Mini International Neuropsychiatric Interview. Fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 31 publications
5
49
1
1
Order By: Relevance
“…Several case reports and prospective studies suggest that women who experience premenstrual symptom exacerbation are more likely to have a highly symptomatic and relapse prone illness 544, 545. One of the largest studies (n = 1099) found that women who met DSM‐5 provisional criteria for premenstrual dysphoric disorder (PMDD) had an earlier illness onset, more comorbid Axis I disorders, a higher number of hypomanic/manic and depressive episodes, and higher rates of rapid cycling 546. In this study, there was a closer gap between BD onset and age of menarche in women with comorbid PMDD, which suggests that sensitivity to endogenous hormones may influence the onset and the clinical course of BD.…”
Section: Specific Populationsmentioning
confidence: 99%
“…Several case reports and prospective studies suggest that women who experience premenstrual symptom exacerbation are more likely to have a highly symptomatic and relapse prone illness 544, 545. One of the largest studies (n = 1099) found that women who met DSM‐5 provisional criteria for premenstrual dysphoric disorder (PMDD) had an earlier illness onset, more comorbid Axis I disorders, a higher number of hypomanic/manic and depressive episodes, and higher rates of rapid cycling 546. In this study, there was a closer gap between BD onset and age of menarche in women with comorbid PMDD, which suggests that sensitivity to endogenous hormones may influence the onset and the clinical course of BD.…”
Section: Specific Populationsmentioning
confidence: 99%
“…This systematic review also highlighted the lack of rsFC research on sex, menstrual cycle phase or menstrual cycle disorders in studies that investigated women of reproductive age. This may be important for numerous reasons: the clinical course of bipolar disorder has been shown to progress differently in men and women, 67 with women reporting greater symptoms of depression and more lability in mood resulting from hormonal fluctuations; 68,69 and an increasing body of literature that has found women with bipolar disorder report higher rates of premenstrual syndrome and premenstrual dysphoric disorder (PMDD) than controls. [70][71][72][73] Further, these differences also extend to brain structure and function: a recently published study found differences in cortical thickness, rsFC and the volume of the caudate nucleus in women with bipolar disorder and comorbid PMDD compared with women who have bipolar disorder without a comorbid diagnosis of PMDD.…”
Section: Limitationsmentioning
confidence: 99%
“…35 Patients with comorbid BD and PMDD showed an earlier age of BD onset, more frequent acute mood episodes and a higher rate of rapid cycling. 36 Two different comorbidity studies pointed out that PMDD seems to be more frequent in BD type II (BD-II), with respect to BD type I (BD-I) patients. 37,38 On the other hand, the possible confounding effect of a higher medication load, which might reduce the comorbidity rate suppressing the PMDD symptoms in BD-I, should be taken into account.…”
Section: Introductionmentioning
confidence: 99%